Cystic fibrosis, third edition. Issue 1 (21st December 2007) - Pollock, Ian
Abstract : Edited by Margaret E Hodson, Andrew Bush and Duncan Geddes. Published by Hodder Arnold, London, 2007, pp 486, £99 (hardback). ISBN 10 0-340-90758-4